Pelatihan Penerapan Akuntansi Digital Menggunakan Aplikasi SIAPIK Pada UMKM Usaha Bersama - Astikawati, Yunita; Bobi, Yopinus; Dewiwati Pelipa, Emilia; Marganingsih, Anna; Triana Relita, Dessy; Suriyanti, Yulia; Dominggus Sore, Avelius (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The preparation of financial reports for small and medium enterprises that are not in accordance with SAK EMKM and the problem of business funding are the main problems for MSMEs. MSMEs when they need funding are asked to present business financial reports, but in reality many umkm have not made these financial reports. This causes limited access for umkm to develop their business. Therefore, this training is conducted to provide knowledge and skills for business actors in recording accounting and preparing financial reports. The recording and preparation process uses the SIAPIK application which has been adjusted to SAK EMKM. The implementation method to improve SIAPIK literacy is divided into several stages, namely socialization, training and training of trainers. The results of this training are that business actors have insight and expertise in preparing financial reports digitally. The implication of this activity is that business actors can control business finances in real time and can develop business. The resulting financial statements are also in accordance with SAK EMKM and are expected to be a means to facilitate business actors to obtain funding. Business actors can also make the right business decisions.